Seasonal Variation on Adventitious Rooting in Branch Cuttings of Pongamia pinnata Pierre - Palanisamy, K.; Kumar, Pramod (Indian Forester, 1997)
The seasonal influence of auxins (IAA, IBA, NAA) on adventitious root formation in the cuttings of Pongamia pinnata was studied. 800 ppm IBA induced 100% rooting and more number of roots in march. Exogenously applied auxins are sensitive to activate the cambium resulting adventitious root formation in a particular season probably when the cambium is in active phase.